Antimicrobial effect of the Biotronic® Top3 supplement and efficacy in protecting rainbow trout (Oncorhynchus mykiss) from infection by Aeromonas salmonicida subsp. salmonicida. (October 2017) - Menanteau-Ledouble, Simon; Krauss, Ines; Goncalves, Rui Alexandre; Weber, Barbara; Santos, Gonçalo Abreu; El-Matbouli, Mansour
Abstract: Demand for more environmentally friendly practices have led to the adoption of several feed supplements by the fish farming industry. In the present study, we investigated a commercially available formula that includes a mixture of three compounds: organic acids, a phytochemical and Biomin® Permeabilizing Complex. This mixture demonstrated antimicrobial properties in vitro and was able to inhibit growth of multiple species of aquatic bacterial pathogens, including Aeromonas salmonicida . Bacterial challenge was performed using A. salmonicida and three exposure routes: intra-peritoneal injection, immersion, and cohabitation. Mortality rates following infection by injection were significantly decreased in the fish that had received the supplemented feed. Fish infected through the other routes did not show a significant difference in mortality. In term of farming performance, while the fish that had received the feed supplement showed an improvement in weight gain and final weight, these changes were not found to be statistically significant. Similarly, no significant difference was observed in the feed conversion ratio. The results of this study suggest that this feed supplement may be effective at protecting rainbow trout from fish furunculosis. Highlights: Biotronic® Top3 is a commercially available feed supplement. It is mixture of organic acids, a permeabilizing complex and a phytochemical. Biotronic® Top3 is inhibitory against aquatic bacterial pathogens in vitro. It can protect fish from infections with the pathogen Aeromonas salmonicida in vivo. It has no effect on growth parameters of the fish.